2020
DOI: 10.1177/0033354920967302
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Syphilis Screening in the Emergency Department

Abstract: The incidence of syphilis infections is on the rise, particularly among African American men and men who have sex with men, and it is reaching epidemic levels in these communities throughout the United States. Although syphilis is relatively inexpensive to treat and cure and is a predictor for HIV incidence among men and transgender women who have sex with men, rates of co-screening for syphilis are low in the emergency department setting, with a dearth of literature on this topic since the 1990s and early 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, universal screening at the WRSU captured cases that would not have otherwise qualified for testing under the CDC STI Treatment Guidelines, 4 a finding that has been reported elsewhere. 23 Thus, the elevated proportion of late latent diagnoses at the WRSU (>60%), as compared with the nationally reported rate of <40%, 1 is likely partially inflated and represents at least some misclassification of cases that are truly early latent. To explore these, we note that of the 170 cases staged as late latent or syphilis of unknown duration, 38 cases (22%) had RPR titers ≥1:64, a cutoff that can be used to distinguish early latent cases.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, universal screening at the WRSU captured cases that would not have otherwise qualified for testing under the CDC STI Treatment Guidelines, 4 a finding that has been reported elsewhere. 23 Thus, the elevated proportion of late latent diagnoses at the WRSU (>60%), as compared with the nationally reported rate of <40%, 1 is likely partially inflated and represents at least some misclassification of cases that are truly early latent. To explore these, we note that of the 170 cases staged as late latent or syphilis of unknown duration, 38 cases (22%) had RPR titers ≥1:64, a cutoff that can be used to distinguish early latent cases.…”
Section: Discussionmentioning
confidence: 98%
“…This framework requires prenatal services as an entry point to the cascade. This restricts our understanding of persons who may not receive prenatal care but do receive testing and treatment, an important limitation as the continued rise in rates of CS necessitates additional resources, including testing and treatment for pregnant persons in settings outside of traditional prenatal care 4,5 . As we work to develop new strategies to curb the growing epidemic of CS, we sought to clarify and organize elements of the current framework for missed prevention opportunities into a primary prevention cascade focused on successful testing and treatment.…”
mentioning
confidence: 99%
“…This restricts our understanding of persons who may not receive prenatal care but do receive testing and treatment, an important limitation as the continued rise in rates of CS necessitates additional resources, including testing and treatment for pregnant persons in settings outside of traditional prenatal care. 4,5 As we work to develop new strategies to curb the growing epidemic of CS, we sought to clarify and organize elements of the current framework for missed prevention opportunities into a primary prevention cascade focused on successful testing and treatment. The goal of this work is to allow us to better describe regional and local targets for intervention with tangible goals, as well as account for a shifting health care landscape in the context of a rapidly growing epidemic.…”
mentioning
confidence: 99%
“…The emergency department (ED) is a frequent site for STI screening and treatment, and the ED setting plays an emerging role in public health interventions for STIs 8 . Screening for HIV in the ED has assisted in the identification of new cases and linkage to treatment, 8,9 and ED-based syphilis screening programs have had similar results 10,11 . However, even when patients receive testing for other STIs such as gonorrhea (GC) and chlamydia in the ED, rates of concurrent testing for syphilis and HIV are low, 12–14 despite CDC/USPSTF recommendations for screening because of shared risk factors for these diseases.…”
mentioning
confidence: 99%
“…8 Screening for HIV in the ED has assisted in the identification of new cases and linkage to treatment, 8,9 and ED-based syphilis screening programs have had similar results. 10,11 However, even when patients receive testing for other STIs such as gonorrhea (GC) and chlamydia in the ED, rates of concurrent testing for syphilis and HIV are low, [12][13][14] despite CDC/USPSTF recommendations for screening because of shared risk factors for these diseases. Previous studies in the ED setting found that among patients tested for GC and chlamydia, rates for HIV cotesting ranged between 3% and 16%, 13,15,16 and rates for syphilis cotesting ranged from 27% to 37%.…”
mentioning
confidence: 99%